Power and Resources in Negotiation: How Power Balance Influences Negotiation Outcomes - Putri Estefania; Ario Anggoro; Diaz Fadilla; Anita A; Alex Ferguson Ginting (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the relationship between power, resources, and power balance in negotiation from a humanistic perspective, which views negotiation as an interpersonal interaction process that upholds dignity, fairness, and relational ethics. Power in negotiation emerges from the strategic use of resources such as information, time, alternatives (BATNA), and formal position, which dynamically interact to shape a negotiator’s capacity to influence. Power imbalances affect communication, decision-making, strategies employed, and the psychological conditions of the parties involved. Dominant parties tend to control the negotiation process, while weaker parties often experience emotional pressure and strategic limitations, increasing the risk of domination and exploitation. Negotiation outcomes typically favor the stronger side, yet such outcomes may threaten the sustainability of long-term relationships. Mitigation strategies include strengthening BATNA, managing information, using objective standards, and building coalitions. This study highlights that negotiation effectiveness and relationship sustainability depend on the ethical and humane application of power.